DIGITAL EDUCATIONAL ENVIRONMENT AS A CONDITION FOR EFFECTIVE STAFF TRAINING FOR INNOVATION ECONOMY - Korzh, Tatyana N.; Sivtseva, Aleksadra S.; Mirontseva, Svetlana S.; Spirina, Yuliya P.; Nikitina, Ekaterina V. (Russian Journal of Education and Psychology, 2024)
The research focuses on the formation of a digital educational environment (DEE) as a crucial factor for training personnel capable of thriving in an innovative economy. Purpose. The study addresses the challenges posed by the rapidly evolving digital business landscape, emphasizing the need for educational institutions to adapt by creating a competitive DEE. The primary goal is to identify the key directions for developing a DEE that effectively prepares students for the demands of the digital economy. Materials and methods. The research utilized various methods, including systematic and functional approaches, expert assessments, and statistical analysis, to evaluate the potential of the educational environment in training digital business professionals. A case study was conducted at Sevastopol State University. The study compared traditional teaching methods with a blended learning model. Results. The authors conclude that a well-designed DEE, leveraging platforms like Moodle (Modular Object-Oriented Dynamic Learning Environment), is essential for preparing future professionals in the digital economy. The results of the research are recommended for use in frameworks for additional professional training, employment, and staff retraining, with the aim of enhancing the overall professional competence of specialists. EDN: SDTYXF